William Findley letter - Findley, William, 1741 or 1742-1821.
ALS (1814 April 11; Washington) from Findley to Manuel Lyres, a merchant of Philadelphia, Pa., pertaining primarily to repeal of the embargo on trade with the British.
U.S. representative from Pennsylvania.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lyres, Manuel -- Correspondence; Embargo; Great Britain -- Commerce -- United States; United States -- Commerce -- Great Britain; United States -- History -- War of 1812.; Representatives, U.S. Congress -- Pennsylvania